Stress Matters Revisited: A Boundary Change Experiment. Issue 10 (October 2013) - Breen, Mara; Clifton, Charles
Breen and Clifton (Stress matters: Effects of anticipated lexical stress on silent reading. Journal of Memory and Language, 2011, 64, 153–170) argued that readers' eye movements during silent reading are influenced by the stress patterns of words. This claim was supported by the observation that syntactic reanalysis that required concurrent metrical reanalysis (e.g., a change from the noun form of abstract to the verb form) resulted in longer reading times than syntactic reanalysis that did not require metrical reanalysis (e.g., a change from the noun form of report to the verb form). However, the data contained a puzzle: The disruption appeared on the critical word ( abstract, report ) itself, although the material that forced the part of speech change did not appear until the next region. Breen and Clifton argued that parafoveal preview of the disambiguating material triggered the revision and that the eyes did not move on until a fully specified lexical representation of the critical word was achieved. The present experiment used a boundary change paradigm in which parafoveal preview of the disambiguating region was prevented. Once again, an interaction was observed: Syntactic reanalysis resulted in particularly long reading times when it also required metrical reanalysis. However, now the interaction did not appear on the critical word, but only following the disambiguating region. This pattern of results supports Breen and Clifton's claim that readers form an implicit metrical representation of text during silent reading.